Desain Pengontrolan Starting Motor Induksi Tiga Phasa Berkapasitas 2.5 MW Dengan Menggunakan Auto Transformator - Ganda Muharetana; Noveri Lysbeti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Three phase induction motor is very widely used as a driving force in the industry because manyhave the advantage, but there are also disadvantages. Advantages of three phase induction motorthat is strong and sturdy, cheap and reliable, high efficiency on the state of normal work, andperawatanya easy, while weaknesses such as the current starting of the initial reach five to seventimes the nominal current motor work full load, especially for motor big power. Use of the methodof induction motor starting using autotransformator can reduce the starting current induction motorso that the motor starting currents induced not by starting to use the method of direct on line (DOL).The use of multiple tap for starting a good thing to do because it can prevent the starting current issuddenly soared, so that the starting current could rise bertahap.Adapun objectives of workmanshipof this study are: Designing Control Design Three Phase Induction Motor Starting Capacity 2.5MW With using Autotransformator, so that it can cope with the weakness of the current inductionmotor in the form of initial starting of reaching five to seven times.Keywords : Induction Motor Starting, Autotransformator